Preventing Tax Evasion: The Moral Strength of Taxpayers and The Power of Tax Authorities - Retnaningtyas Widuri; Yenni Mangoting; Arja Sadjiarto; Tonny Stephanus (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of coercive power and the legitimacy of the tax authority on the morale of taxpayers to prevent tax evasion. This study conducts a moderation test to determine the role of tax morale. This study uses a survey approach by distributing 100 questionnaires and analyses them using Partial Least Square (PLS). The results prove that the morale of taxpayers is a force to prevent tax evasion. A moderation test proves that tax morals can weaken the influence of government coercion on tax avoidance. Tax morale strengthens the influence of legitimate power on tax avoidance, although the government's legitimate power does not directly affect tax avoidance. This study explains that taxpayer fraud can be anticipated by enforcing government power through sanctions and audits accompanied by moral strength. The moral strength of taxpayers is a factor that plays a role in controlling government behaviour.